(untitled) (Research, Society and Development, 2018)
The present study had the objective of verifying the perception of the multiprofessional team regarding the search of elderly people for medical care in a Basic Health Unit of a municipality in the interior of Vale do Taquari / RS. This is a descriptive and exploratory research, with a qualitative approach, performed with nine professionals from the multiprofessional team. The results were guided by the professionals’ perceptions about the consultations performed by the elderly in the referred unit, as well as the main factors related to their demand, being doctor’s follow-up, requesting exams or medication. It was also observed that the medicalization of the population influences the search for consultations, acting directly on questions of serviceability. Therefore, it can be concluded that the demand for medical consultations in the third age does not always have a plausible reason, being essential to carry out a joint action between the professionals and the management to try to solve this public health problem.